Generation Z's Interest in Islamic Banks and Conventional Banks: An Analysis Based on Sustainability and Financial Ethics Aspects - Adinda Putri Lestari; MH Ainulyaqin; Kisanda Midisen; Sakum Sakum; Yudianto Achmad (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of sustainability and financial ethics on Generation Z's interest in Islamic banks and conventional banks, and to identify the differences in the influence of these two aspects in each banking system. The study used a quantitative approach with a survey method by distributing questionnaires to 143 Generation Z respondents domiciled in Bekasi and selected using a purposive sampling technique. Data analysis was performed using multiple linear regression with the help of SPSS software. The results show that sustainability and financial ethics have a positive and significant effect on Generation Z's interest in both Islamic banks and conventional banks. In the Islamic bank model, the sustainability aspect obtained a coefficient value of 0.442 and financial ethics of 0.483, while in the conventional bank model, the sustainability aspect obtained a coefficient value of 0.590 and financial ethics of 0.275. The results also show that financial ethics is a more dominant factor in Islamic banks, while the sustainability aspect is more dominant in conventional banks. In addition, the Adjusted R Square value of 95.1% in Islamic banks and 92.9% in conventional banks indicates that the research model has a high explanatory ability towards Generation Z's interest. This study shows that Generation Z's financial preferences are not only influenced by economic aspects, but also by ethical values and sustainability orientation in determining the choice of banking services.